Kinds of kindness [videorecording (Blu-Ray)] - Lanthimos, Yorgos, 1973-; Filippou, Efthimis, 1977-; Stone, Emma, 1988-; Plemons, Jesse, 1988-; Dafoe, Willem; Qualley, Margaret; Chau, Hong, 1979-; Alwyn, Joe; Athie, Mamoudou, 1998-; Schafer, Hunter, 1998- (Searchlight Pictures, 2024)
A triptych fable, following a man without choice who tries to take control of his own life; a policeman who is alarmed that his wife who was missing-at-sea has returned and seems a different person; and a woman determined to find a specific someone with a special ability, who is destined to become a prodigious spiritual leader.